Environment predicts seagrass genotype, phenotype, and associated biodiversity in a temperate ecosystem - Alotaibi, Nahaa M; Kenyon, Emma J; Bertelli, Chiara M; Al-Qthanin, Rahmah N; Mead, Jessica; Parry, Mark; Bull, James C (Frontiers in Plant Science, 2022)
Coastal vegetative ecosystems are among the most threatened in the world, facing multiple anthropogenic stressors. A good example of this is seagrass, which supports carbon capture, coastal stabilization, and biodiversity, but is declining globally at an alarming rate. To understand the causes and consequences of changes to these ecosystems, we need to determine the linkages between different biotic and abiotic components. We used data on the seagrass, Zostera marina, collected by citizen scientists across 300 km of the south coast of the United Kingdom as a case study. We assembled data on seagrass genotype, phenotype, infauna, and associated bathymetry, light, sea surface temperature, and wave and current energy to test hypotheses on the distribution and diversity of this temperate sub-tidal ecosystem. We found spatial structure in population genetics, evident through local assortment of genotypes and isolation by distance across a broader geographic scale. By integrating our molecular data with information on seagrass phenotype and infauna, we demonstrate that these ecosystem components are primarily linked indirectly through the effects of shared environmental factors. It is unusual to examine genotypic, phenotypic, and environmental data in a single study, but this approach can inform both conservation and restoration of seagrass, as well as giving new insights into a widespread and important ecosystem.